Numerical performance of a new algorithm for performing modal analysis of full-scale reinforced concrete structures that are Dιscrεtized with the HYMOD approach - Gravett, Dewald Z.; Mourlas, Christos; Markou, George; Papadrakakis, Manolis (My University, 2019)
Nonlinear dynamic modeling of full-scale mid- and high-rise reinforced concrete structures through the use of the 3D detailed approach that foresees the use of hexahedral elements with embedded rebars is not yet feasible due to numerous reasons. The two main numerical problems that do not allow for this type of analysis to be performed, are the numerical instabilities that immerse when the opening and closing of cracks initiates during the dynamic analysis and the excessive computational demand that is required even when dealing with small numerical models. This work will present the computational response of a newly developed algorithm that is used herein to perform modal analysis of large-scale models. The under study algorithmic development is a part of a project that aims towards alleviating the prementioned numerical constraints in regard to performing nonlinear dynamic analysis of full-scale reinforced concrete structures. An extensive numerical investigation is presented that foresees the performance of modal analysis on different full-scale reinforced concrete structures that are discretized with the Hybrid Model (HYMOD) approach. Based on the numerical investigation findings, the developed algorithm was found to be computationally efficient offering a robust numerical tool for performing modal analysis of large-scale numerical models.